Mesenchymal stem cells of Oravka chicken breed: promising path to biodiversity conservation - Svoradová, Andrea; Vašíček, Jaromír; Zmrhal, Vladimír; Venusová, Eva; Pavlík, Aleš; Bauer, Miroslav; Olexiková, Lucia; Langraf, Vladimír; Sláma, Petr; Chrenek, Peter (Poultry science, 2023)
Mesenchymal stem cells (MSCs) are multilineage cells able to differentiate into other cell types. MSCs derived from bone marrow or compact bones are the most accessible stem cells used in tissue engineering. Therefore, the aim of this study was to isolate, characterize and cryopreserve MSCs of endangered Oravka chicken breed. MSCs were obtained from compact bones of the femur and tibiotarsus. MSCs were spindle-shaped and were able to differentiate into osteo-, adipo-, and chondrocytes under the specific differentiation conditions. Furthermore, MSCs were positive for surface markers such as CD29, CD44, CD73, CD90, CD105, CD146 and negative for CD34CD45 by flow cytometry. Moreover, MSCs demonstrated high positivity of "stemness" markers aldehyde dehydrogenase, alkaline phosphatase as well as for intracellular markers vimentin, desmin, α-SMA. Subsequently, MSCs were cryopreserved using 10% dimethyl sulfoxide in liquid nitrogen. Based on the results from the viability, phenotype, and ultrastructure assessment we can concluded that the MSCs were not negatively affected by the cryopreservation. Finally, MSCs of endangered Oravka chicken breed were successfully stored in animal gene bank, thus making them a valuable genetic resource.
Keywords: buněčná diferenciace; Stem Cells; Mesenchymal Stem Cells; Cell Differentiation; flow cytometry; stem cell; Cells, Cultured; fenotyp; kur domácí; Chickens; kmenové buňky; Phenotype; Animals; zvířata; mezenchymální kmenové buňky; kultivované buňky; chicken; native breed; cryopreservation